Oxidative stress markers in patients suffering from opioid and psychostimulant dependence syndrome - I. M. Bykov; D. A. Lubchenko; K. A. Popov; Ya. Ye. Denisova; A. N. Stolyarova; M. A. Popova (Инновационная медицина Кубани, 2020)
Background. The available data from clinical studies suggest the essential role of free radical processes in the pathogenesis of drug dependence syndrome. At the same time, there is a limited understanding of using markers of oxidative stress in laboratory monitoring and prediction of drug pathology.Objective. To characterize changes in promising indicators of oxidative stress in patients with psychostimulant and opioid dependence syndrome.Material and Methods. The total study population was divided into three groups of men aged 23–35: healthy controls (n = 20), patients with the opioid (n = 20) and psychostimulant (n = 20) dependence syndrome. Patients were analyzed for the oxidative stress markers while being in therapy for addiction syndrome aimed at treating mental disorders and detoxification.Results. The study of antioxidant activity and blood plasma thiol groups did not reveal any significant differences between patients suffering from opioid and psychostimulant addiction. The values of the parameters mentioned above were maintained by 20–30% lower than the control indices throughout the entire study. The nature of changes in erythrocyte suspension parameters was not so unambiguous. Thus, patients with opioid dependence syndrome were characterized by a 91% increase in thiobarbituric acid (TBA)-reactive materials in the setting of a slightly altered state of the glutathione system parameters. Psychostimulant dependent patients revealed relatively low level of the products of biomolecule oxidative modifications in the erythrocytes that is 52% higher compared to the control values. It decreased during the therapy, but glutathione concentration reduction by 33% and an imbalance of glutathione metabolism were determined.Conclusion. The course of the opioid dependence syndrome is characterized by a pronounced intensification of free radical processes while the common trait for psychostimulant abusers is significant changes in the antioxidant defense system. Therefore, in the first case, it is most justified to conduct a laboratory assessment of indicators of oxidative damage, and in the second one, it is also advisable to determine the markers of the state of individual links of the antioxidant system.